Genome-wide identification and expression analysis of the HVA22 gene family in cotton and functional analysis of GhHVA22E1D in drought and salt tolerance - Zhang, Haijun; Yuan, Yanchao; Xing, Huixian; Xin, Ming; Saeed, Muhammad; Wu, Qi; Wu, Jing; Zhuang, Tao; Zhang, Xiaopei; Mao, Lili; Sun, Xuezhen; Song, Xianliang; et al. (Frontiers in Plant Science, 2023)
The HVA22 family of genes are induced by abscisic acid and stress, encodes a class of stress response proteins with a conserved TB2/DP1/HVA22 domain that are unique among eukaryotes. Previous studies have shown that HVA22s play an important role in plant responses to abiotic stresses. In the present study, 34, 32, 16, and 17 HVA22s were identified in G. barbadense, G. hirsutum, G. arboreum and G. raimondii, respectively. These HVA22 genes were classified into 9 subgroups, randomly distributed on the chromosomes. Synteny analysis showed that the amplification of the HVA22s were mainly due to segmental duplication or whole genome replication (WGD). Most HVA22s promoter sequences contain a large number of drought response elements (MYB), defense and stress response elements (TC-rich repeats) and hormone response elements (ABRE, ERE, SARE, etc.), suggesting that HVA22s may respond to adversity stresses. Expression profiling demonstrated that most GhHVA22s showed constitutive expression pattern in G. hirsutum, and could respond to abiotic stresses such as salt, drought and low temperature. Overexpression of GhHVA22E1D (GH_D07G0564) in Arabidopsis thaliana enhances salt and drought tolerance in Arabidopsis. Virus induced gene silencing of GhHVA22E1D reduced salt and drought tolerance in cotton. This indicates that GhHVA22E1D plays an active role in the plant response to salt stress and drought stress. GhHVA22E1D may act in plant response to adversity by altering the antioxidant capacity of plants. This study provides valuable information for the functional genomic study of the HVA22 gene family in cotton. It also provides a reference for further elucidation of the functional studies of HVA22 in plant resistance to abiotic stress response.